Development of management of emergency surgical care for patients with acute traumatic and nontraumatic spinal pathologies in conditions of megapolis - A. K. Dulaev; V. A. Manukovskiy; D. I. Kutyanov; Yu. Yu. Bulakhtin; S. L. Brizhan’; P. V. Zhelnov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors developed the management strategy of emergency care for patients with acute spinal surgical pathology in conditions of megapolis. MATERIAL AND METHODS. A comparative statistical analysis was made in 2627 patients. The patients (n =777) underwent treatment in multicenter hospitals of emergency care of the spine (decentralized system). The other patients (n = 1850) were treated in Municipal Center of Emergency Surgery of the Spine (centralized system). RESULTS. It is appropriate to establish departments of emergency surgery of the spine on the base of separate multicenter hospitals in megapolis. These hospitals should be properly equipped and they should have specially trained doctors and nurses, stable financing, effective management on admission to hospital. CONCLUSIONS. The efficacy of proposed measures allowed authors to recommend them to wide practical application.